Population, ethnicity, and nation-building - Goldscheider, Calvin (Boulder Westview Press, 1995)
This volume focuses on the linkages between ethnicity and population processes in the context of nation-building. Using historical and contemporary illustrations in a variety of countries, parts of this complex puzzle are scrutinized through the prisms of sociology, history, political science, anthropology, and demography. Themes of ethnic group formation and transformation, persistence and assimilation, demographic transitions and convergences, and the processes of political mobilization and economic development are described and compared. Case studies from Southeast Asia, China, Africa, Brazil, Israel, the former Soviet Union, Canada, Europe, and the United States are presented by leading scholars. The examples illustrate the diversity of contexts that connect population, ethnicity, and nation-building, raising new questions and comparative problems.
Population, ethnicity, and nation-building: themes, issues, and guidelines / Calvin Goldscheider -- Ethnic diversity and change in Southeast Asia / Charles Hirschman -- Economic patterns, migration, and ethnic relationships in the Tibet Autonomous Region, China / Rong Ma -- Ethnic conflict, history, and state formation in Africa / Philip E. Leis -- Fact and myth: discovering a racial problem in Brazil / Thomas E. Skidmore -- Ethnicity and nation-building in Israel: the importance of demographic factors / Calvin Goldscheider -- Demographic sources of the changing ethnic composition of the Soviet Union / Barbara A. Anderson and Brian D. Silver -- The Cultural partitioning of Canada: demographic roots of multinationalism / Edward T. Pryor -- On the structure of ethnic groups: crisscrossing ties of ethnicity, social class, and politics in Europe / Alan S. Zuckerman -- Ethnic definition, social mobility, and residential segregation in the United States / Michael J. White and Sharon Sassle.
Includes bibliographical references.
PI-8297 donated by Department of Global Development Cornell University Ithaca.
Keywords: National state; Demographic transition; Ethnic groups -- Political activity; Ethnic relations; Population geography